Adherence to Referral Criteria for Burn Patients; a Systematic Review - Bazzi, Ali; Ghazanfari, Mohammad Javad; Norouzi, Masoumeh; Mobayen, Mohammadreza; Jafaraghaee, Fateme; Emami Zeydi, Amir; Osuji, Joseph; Karkhah, Samad (Archives of Academic Emergency Medicine, 2022)
Introduction: Burn injuries are under-appreciated trauma, associated with substantial morbidity and mortality. It is necessary to refer patients in need of specialized care to more specialized centers for treatment and rehabilitation of burn injuries. This systematic review aimed to assess the adherence to referral criteria for burn patients. Methods: An extensive search was conducted on Scopus, PubMed, and Web of Science online databases using the relevant keywords from the earliest to October 7, 2021. The quality of the included studies was assessed using the appraisal tool for cross-sectional studies (AXIS tool). Results: Among a total of 7,455 burn patients included in the nine studies, 60.95% were male. The most frequently burned areas were the hands (n=3) and the face (n=2). The most and least common burn mechanisms were scalds (62.76%) and electrical or chemical (2.88%), respectively. 51.88% of burn patients had met ≥ 1 referral criteria. The overall adherence to the referral criteria for burn patients was 58.28% (17.37 to 93.39%). The highest and lowest adherence rates were related to Western Cape Provincial (WCP) (26.70%) and National Burn Care Review (NBCR) (4.97%) criteria, respectively. Conclusion: The overall adherence to the referral criteria for burn patients was relatively desirable. Therefore, well-designed future studies are suggested in order to uncover approaches to improve adherence to referral criteria for burn patients.